IDENTIFIKASI TANAMAN EUCALYPTUS PELLITA (Eucalyptus pellita F.Muell) YANG TERSERANG HAMA DI PT. MUSI HUTAN PERSADA - Rosianty, S.Hut, M.Si, Yuli; Lensari, Delfy; Aini, Agnes Nurul (Sylva Jurnal Ilmu-ilmu Kehutanan, 2024)
HTI is an industrial plantation forest built in order to increase the potential and quality of production forests by implementing intensive silviculture to meet the needs of industrial raw materials such as wood processing, pulp, and paper. In South Sumatra there is HTI PT. Musi Hutan Persada (MHP) which is one of the largest industrial plantation forest companies in Indonesia. Initially, PT, MHP only planted and produced Acacia Crassicarpa, Acacia Auriculifomis, Acacia Mangium, but now it has been combined with Eucalyptus pellita which is one of the priority types developed in HTI management to obtain its wood fiber. This study was conducted to determine the Eucalyptus pellita plants attacked by pests, the percentage of pest attacks and the level of damage caused by pests. The research method used is a quantitative method, by making transects and observations of Eucalyptus pellita attacked by pests. There are three types of pest attacks found, namely the Zeuzera coffea pest attack on Eucalyptus pellita plants with symptoms of fractures at the base of the stem, swelling and hollow stems. Homona coffearia pest attacks with symptoms of perforated leaves and cut leaf edges or bite marks from pests. Symptoms of Helopeltis sp attacks with symptoms of punctures on the leaves that can cause the leaves to dry and die or if they are still growing the surface of the leaf skin cracks and shrivels. The percentage of Zeuzera coffea pest attacks occurs more in old plants at the age of 6 months only ± 0.002%, the age of 16 months increases ± 0.0277% and at the age of 26 months it is even higher to 0.0580%. While for Homona coffearia and Helopeltis sp pests, they attack young plants more, the older the plant the percentage of pest attacks decreases. During the two-month observation, the percentage of Homona coffearia attacks decreased from 0.0048% to 0.0030%. Likewise with the percentage of Helopeltis sp attacks 0.0090% to 0.0089%. The level of damage to plants due to Zeuzera coffea pests increases with increasing age in plants aged 6 months (0.0004%), 16 months (0.0071%), 26 months (0.0076%). While the level of damage due to Homona coffearia and Helopeltis sp decreases with increasing age of the plant, damage from leaf rollers from 0.0012% to 0.0007%. The level of shoot damage from 0.0023% to 0.0022%.